Pandangan Hukum Islam tentang Hidup Serumah setelah Talak Bain Kubra di Desa Way Urang Lampung Selatan - Ayub Sutiawan; Abdul Qodir Zaelani; Maimun Maimun; Yusuf Baihaqi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to analyze the perspective of Islamic law on the practice of cohabitation after the occurrence of talak bain kubra (triple divorce), focusing on a literature-based analysis of primary Islamic legal sources such as the Qur’an, Hadith, scholars’ opinions, and classical as well as contemporary fiqh literature. This research is a library study (library research) employing normative juridical and conceptual approaches. Data were obtained through a review of classical fiqh texts from the four schools of thought (madhhab), Qur’anic exegesis, scholarly works, and legal provisions related to Islamic family law. The findings indicate that, according to Islamic law, cohabitation between a man and a woman after the occurrence of talak bain kubra is prohibited and considered unlawful (haram). Based on the Qur’an, Surah Al-Baqarah (2:230), it is stated that if a husband divorces his wife for the third time, it is not lawful for him to remarry her unless she has lawfully married another man and that marriage ends naturally. This view is supported by the majority of scholars from the Shafi‘i, Hanafi, Maliki, and Hanbali schools, who agree that talak bain kubra completely dissolves the marital bond (faskhun nikah), and a remarriage can only occur after the condition of tahlil has been fulfilled in accordance with Sharia. The analysis of fiqh literature further reveals that cohabitation without a valid marriage contract after talak bain kubra contradicts the principles of ‘iffah (chastity) and hifz an-nasl (protection of lineage), which are integral parts of the objectives of Islamic law (maqasid al-shari‘ah). From a social standpoint, such practices often arise due to low Islamic legal literacy, economic constraints, and misconceptions regarding the concept of ruju‘ (reconciliation) in Islam. This study concludes that cohabitation after talak bain kubra, from the perspective of Islamic law, constitutes a clear violation of definitive (qat‘i) religious injunctions. Therefore, it is necessary to enhance public understanding through Islamic legal education and scholarly-based religious outreach to ensure awareness of the legal boundaries governing marital relations after a triple divorce.